Information Factor Color Revolutions and Modern Technology Dismantling of Political Regimes - A. V. Manoylo (Vestnik MGIMO-Universiteta)
This article analyzes the problems associated with the dismantling of the political regimes in modern states (both authoritarian and democratic type) and the role of technology in the process of color revolutions. Problems of dismantling of political regimes and the associated problems of color revolutions acquire extreme urgency and actuality in modern conditions. In the world history always there were problems associated with the dismantling of the political regimes. But formerly the instruments of dismantling included mostly violent methods in the classical sense, applied in armed coups, local armed conflicts, civil wars and military interventions. And the international community managed to develop effective methods to counter these threats and to create effective mechanisms for political control of these processes, even at the international level. Acuteness of the problem associated with the threat of military coups in the various countries of the world does not cease to be actual and not removed from the agenda, but for the whole international community this category of threats is familiar, and the world community knows how to react to it. However, today the world is changing, and technologies of armed coups are replaced by more subtle color revolutions technology that is cleverly disguised as a true revolutionary movement and virtually unopposed from both- countries witch fully developed democracy and of the Oriental type, preserved traditional livelihoods. Repetition of the scenario of color revolutions in Ukraine causes legitimate concern (well founded anxiety), since there is growing confidence that Ukraine -not the end point of this scenario, but simply a bargaining chip to the geopolitical game in which the brunt of American directors (producers) of color revolutions may be directed to Russia, China and Kazakhstan.